2019
DOI: 10.1097/psy.0000000000000704
|View full text |Cite
|
Sign up to set email alerts
|

Neural Processing of Food and Erotic Cues in Bulimia Nervosa

Abstract: Objective Event-related brain potential (ERP) studies have shown that bulimia nervosa (BN) is associated with facilitated processing of disorder-specific stimuli, visible in altered early components during presentation of food cues and bodies varying in size. Less is known about BN and late ERPs, typically less influenced by perceptual features and regarded as more reliable indices of motivational relevance. The purpose of this study was to use the late positive potential (LPP) to investigate the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…It has been shown that personally signi cant stimuli, such as faces of loved ones or cues of personal phobias, are associated with high levels of physiological reactivity (38,39). In our previous study (6), the presentation of personal binge food cues successfully prompted subjective feelings of arousal that were higher than those observed using nonpersonal high-calorie food cues. Thus, during a telephone interview, participants reported their six personal binge foods, describing them meticulously and giving at least two descriptors of each food (e.g., lasagna with meat, cheese, and bechamel).…”
Section: Stimulimentioning
confidence: 71%
See 2 more Smart Citations
“…It has been shown that personally signi cant stimuli, such as faces of loved ones or cues of personal phobias, are associated with high levels of physiological reactivity (38,39). In our previous study (6), the presentation of personal binge food cues successfully prompted subjective feelings of arousal that were higher than those observed using nonpersonal high-calorie food cues. Thus, during a telephone interview, participants reported their six personal binge foods, describing them meticulously and giving at least two descriptors of each food (e.g., lasagna with meat, cheese, and bechamel).…”
Section: Stimulimentioning
confidence: 71%
“…Patients with this debilitating disorder are characterized by binge eating, inappropriate compensatory behaviors, undue in uence of body weight and/or shape on self-esteem (4). These symptoms appear to be related to altered food cue responses, although it recently emerged that erotic stimuli also tend to be processed differently in patients with BN, at least in terms of subjective emotional reactivity (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Delgado-Rodríguez et al ( 2019 ) conducted an ERP study to evaluate the LPP response to food and erotic cues in individuals with BN. The authors hypothesized that as these individuals exhibit aversion to body cues, the motivational significance of erotic images could be increased in women with BN.…”
Section: Resultsmentioning
confidence: 99%
“…The 15 included studies scored from 5 to 9 on the modified Newcastle-Ottawa Quality Assessment Scale. Two studies (Rodriguez et al, 2007 ; Blechert et al, 2011a ) reached scores of 5 or 6, nine studies (Léonard et al, 1998 ; Otagaki et al, 1998 ; Tammela et al, 2010 ; Kuehnpast et al, 2012 ; Merlotti et al, 2013 ; Mai et al, 2015 ; Wolz et al, 2017 ; Leehr et al, 2018 ) 7 or 8, and four studies (Blechert et al, 2011b ; Imperatori et al, 2015 ; Schienle et al, 2017 ; Delgado-Rodríguez et al, 2019 ) scored 9. The major weaknesses found in the studies included (1) absence of sample size calculation, (2) comparability of the groups (e.g., large differences between subgroup characteristics, such as BMI) and (3) the absence of a standardized and paired stimulus used in the tasks.…”
Section: Resultsmentioning
confidence: 99%